Energy Storage in Strained Organic Molecules: (Spectro)Electrochemical Characterization of Norbornadiene and Quadricyclane. Issue 12 (20th April 2016) - Brummel, Olaf; Besold, Daniel; Döpper, Tibor; Wu, Yanlin; Bochmann, Sebastian; Lazzari, Federica; Waidhas, Fabian; Bauer, Udo; Bachmann, Philipp; Papp, Christian; Steinrück, Hans‐Peter; Görling, Andreas; et al.
Abstract: We have investigated the electrochemically triggered cycloreversion of quadricyclane (QC) to norbornadiene (NBD), a system that holds the potential to combine both energy storage and conversion in a single molecule. Unambiguous voltammetric traces are obtained for pure NBD and pure QC, the latter a strained polycyclic isomer of the former. The difference in redox potentials is smaller than the energy difference between the neutral molecules. This is owing to a significant energy difference between the corresponding radical cations, as demonstrated by density functional theory (DFT) calculations. The vibrational modes of each pure compound are characterized experimentally in the fingerprint region and identified by DFT methods. Thermal and electrochemical transformations of NBD and QC are monitored in situ by IR spectroelectrochemical methods. The kinetics of the cycloreversion of QC to NBD, which is catalyzed by oxidizing equivalents, can be controlled by an applied electrode potential, which implies the ability to adjust in real time the release of thermal power stored in QC. Abstract : Isomer pair : Norbornadiene and quadricyclane are characterized experimentally and theoretically in terms of electrochemical oxidation potentials, vibrational spectroscopy, and spectroelectrochemical monitoring. The rate of exothermic cycloreversion is controlled through an applied electrode potential. The system has the potential to combine both energy storage and conversion in a single molecule.